Instrument for Integrated Information System Assessment in Higher Learning Institutions - Ruzaini, Abdullah Arshah; Mohammad Ishak, Desa; Ab. Razak, Che Hussin (American Scientific Publisher, 2017)
The need for an instrument to comprehensively assess Integrated Information System (IIS) is crucial in order to provide complete status on IIS effectiveness to the organisation. The instrument is considered comprehensive when it includes all the three main domains of Information System integration namely organisational, technical and strategic domain. This paper discusses on the design and development of IIS assessment instrument, including the testing of the instrument to check on its reliability. The process of constructing assessment statements, the formulation involved in the assessment, and interpreting the results from the assessment are discussed. The proposed instrument is successfully tested and has been proven reliable.